Genetic evolution of PB1 in the zoonotic transmission of influenza A(H1) virus - Gíria, M. (2015)
The epidemiology of human infection with swine-origin influenza A(H1) viruses suggests that the virus must adapt to replicate and transmit within the human host. PB1 is essential to the replication process. The objective of this study was to identify whether PB1 retains genetic traces of interspecies transmission and adaptation. We have found that the evolutionary history of PB1 is traceable. Lineage appears to be distinguished by amino acid changes between the conserved motifs of the viral polymerase, which can have major impact in PB1 protein folding, and by changes in the expression of the Mitochondrial Targeting Sequence and in the predicted helical region, that putatively affect induction of cellular apoptosis by PB1-F2. Furthermore, we found genomic markers that possibly relate to viral adaptation to new hosts and to new cellular environment and, additionally, to an enhanced compatibility with HA. We found no specific trend in the amino acid substitutions. Viral fitness appears to be favored by less reactive amino acids in some positions, while in others more reactive ones are fixed. Also, more flexible conformations appear associated with higher protein stability in general, although often more restrictive conformations appear to have favored protein folding and binding. Several aspects of PB1 mapping domains and the specific roles and interaction of PB1, PB1-F2 and N40 with each other and with other viral proteins and host cellular molecules remain unclear. Tracing the genetic evolution is critical to further understand the mechanisms by which PB1 affects vital fitness and adaptation. This analysis now permits putative adaptive related polymorphisms to be experimentally evaluated for phenotypic impact.